Special needs of disproportionate dwarfs for a multi-use kitchen design - Razal, Rachel Angeli R.
There is an absence of a specific guideline which designers can follow in designing kitchens for households with normal and vertically challenged inhabitants. Due to this gap in Universal Design, people with dwarfism try to create their own remedies to problems they encounter in terms of space use in order to achieve a more convenient and better flow of activity. The main objective of the study is to determine the specific needs of dwarfs in a multi-use kitchen design. It determined the problems that are encountered by dwarfs in kitchen use and identified functional requirements needed by them to properly engage in kitchen activities. Descriptive method was used in this study applying purposive sampling of the ten respondents. These individuals have disproportionate dwarfism and they share common chores and tasks in the kitchen with their normal family members. The study was aided by questionnaires, anthropometric data sheets and kitchen evaluation tools. Tables were used to represent the gathered data from the questionnaires. Obtained anthropometric measures of the respondents were subjected to statistical analysis such as the Test for Normality and One Sample T-test. To understand further how the kitchen is being used by the respondent, a model with the measured anthropometric data was drawn to scale and was plotted into their existing kitchen plans and elevation using Auto Cad. The study identified that among kitchen activities, the most difficult for dwarf users are: (1) washing the dishes, (2) putting things in overhead cabinets and (3) reaching the cooktop. The study verified that existing kitchen design standards are not suited for dwarfs due to the significant difference in their anthropometric measures with that of the normal average man. It concluded the misfit between the body dimensions of disproportionate dwarf respondents and their existing kitchen design. The research also presented several solutions for a more appropriate multi-use kitchen design suited for disproportionate dwarfs. It is an aid in the provision of appropriate working conditions needed by achondroplastic dwarfs in the context of a household environment.